Bacterial desulphurization of low-rank coal: A case study of Eocene Lignite of Western Rajasthan, India. Issue 10 (19th May 2018) - Singh, Alok K.; Kumar, Aniruddha; Singh, Prakash K.; Singh, Asha Lata; Kumar, Alok
ABSTRACT: High sulfur lignite samples collected from Giral mine was subjected to desulfurization using bacteria Burkholderia sp. GR 8–02 isolated from native lignite. A removal of 50.69% of total Sulfur (St ) has been observed. The reduction in hydrogen and ash content was found up to 2.92% and 14.78%, respectively. In addition, relative carbon (up to 12.81%) and nitrogen (up to 34.52%) has also been increased. An increase in the relative concentration of volatile matter and fixed carbon (up to 19.47% & 3.29%) has been detected. In addition, the desulfurization of high sulfur lignite with Burkholderia sp. GR 8–02 increased the calorific value from 5.24% to 20.74%.